SYSTEMATIC LITERATURE REVIEW: PENGEMBANGAN E-COMIC INTERAKTIF BERBASIS PMRI (PENDIDIKAN MATEMATIKA REALISTIK INDONESIA): SOLUSI KREATIF UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN PEMAHAMAN KONSEP SISWA - Salmadhiya Ananda; Nafida Hetty Marhaeni (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2025)
The learning process is essentially a communicative interaction between educators and students, where learning media plays an important role in bridging the delivery of complex material. Along with the development of information technology, the need for innovative and adaptive learning media is becoming increasingly urgent, especially in the context of mathematics learning. Interactive e-comic based on the Indonesian Realistic Mathematics Education (PMRI) approach is one of the potential media alternatives, because it is able to present material contextually, visually, and interestingly for digital generation students. The low mathematical literacy score of Indonesian students based on the results of the Program for International Student Assessment (PISA) in 2022 indicates a weak understanding of basic mathematical concepts and low student learning motivation. However, the utilization of PMRI based interactive e-comic in learning is still very limited, and there are not many studies that simultaneously evaluate its effect on students' learning motivation and concept understanding. This study uses the Systematic Literature Review (SLR) method by analyzing 19 articles from various scientific databases, to identify the effectiveness of PMRI-based interactive e-comics in improving the quality of mathematics learning. The results of this study are expected to contribute to the development of more relevant technology-based learning media, as well as a reference for educators and media developers in designing learning strategies that are more interactive, contextual, and meaningful.